Putusan Mahkamah Konstitusi Tentang Status Anak Luar Nikah Dan Kekuatan Hukumnya - Dadan Muttaqien; Muhammad Arif Zuhri (Unisia, 2013)
The problem of lineage, in relation to Islam, is getting important to be discussed and to be given sufficient attention by Muslims today. This situation is driven by the verdict of the Indonesian Constitutional Court No. 46/PUU-VIII/2010 on the case of children which were born outside marital relation. The said verdict has been considered as controversial and led to prolonged polemics in the society, and particularly among Muslims. This due to the content of the verdict that is not within the boundary of the established norm in Islamic law. One of the negative effects that seems to happen is that adultery will be justified by such verdict, since the children born as result of this adultery is considered as legal from the civil law perspective. This article tries to analyse the topic from the perspective of Islamic law. The article concludes that such verdict has not carry any legal power if it put in the context of Islamic law.Key words: mahkamah konstitusi, status anak, luar nikah